Phacomatosis pigmentokeratotica: a case of HRAS mosaicism causing rhabdomyosarcoma. (1st November 2018) - Prieto‐Barrios, M.; Llamas‐Martin, R.; Velasco‐Tamariz, V.; Calleja‐Algarra, A.; Ruano, Y.; Ortiz‐Romero, P.L.; Rodriguez‐Peralto, J.L.
Summary: A 17‐year‐old male presented with a large sebaceous naevus (SN) comprising part of his right face and scalp and a speckled lentiginous naevus (SLN) on his left trunk, hip, neck and scalp with a checkerboard pattern. His right oral hemimucosa showed extensive papillomatous lesions, which were contiguous with the upper‐lip SN lesions. He also showed extracutaneous manifestations including cardiac, musculoskeletal and ocular alterations. Internally, he had developed two primary rhabdomyosarcomas. DNA samples of the SN, SLN, oral papillomatous hyperplasia and both rhabdomyosarcomas were analysed by Sanger sequencing. An HRAS c.37G>C mutation was detected in all of them. Skin and blood DNA were wild‐type. Phacomatosis pigmentokeratotica (PPK) is characterized by the association of an SN with a papular naevus spilus and extracutaneous manifestations. Until recently, the aetiopathogenetic hypothesis of didymosis was accepted. However, in 2013 Groesser et al . proved the existence of an activating HRAS mutation as the cause of this syndrome. A higher incidence of cancer has been observed in germline RASopathies. Furthermore, up to 30% of human cancers show dysregulation of the Ras–Raf–MEK–ERK pathways. In our patient, an HRAS mosaic mutation explains not only the cutaneous but also the extracutaneous manifestations. To our knowledge this is the first described case of PPK in which the existence of an HRAS mosaic mutation is the confirmed cause of rhabdomyosarcoma. Furthermore, the HRAS c.37G>C mutation has never been related to any type of rhabdomyosarcoma. Mosaicisms could be underdiagnosed causes of childhood tumours. As dermatologists we stand in a privileged position of being able to detect these alterations.